Enhancement of oxidative stress contributes to increased pathogenicity of the invasive pine wood nematode. (14th January 2019) - Zhang, Wei; Zhao, Lilin; Zhou, Jiao; Yu, Haiying; Zhang, Chi; Lv, Yunxue; Lin, Zhe; Hu, Songnian; Zou, Zhen; Sun, Jianghua
Abstract : Reactive oxygen species (ROS) play important roles in defence response of host plants versus pathogens. While generation and detoxification of ROS is well understood, how varied ability of different isolates of pathogens to overcome host ROS, or ROS contribution to a particular isolate's pathogenicity, remains largely unexplored. Here, we report that transcriptional regulation of the ROS pathway, in combination with the insulin pathway, increases the pathogenicity of invasive species Bursaphelenchus xylophilus . The results showed a positive correlation between fecundity and pathogenicity of different nematode isolates. The virulent isolates from introduced populations in Japan, China and Europe had significantly higher fecundity than native avirulent isolates from the USA. Increased expression of Mn-SOD and reduced expression of catalase / GPX-5 and H2 O2 accumulation during invasion are associated with virulent strains. Additional H2 O2 could improve fecundity of Bu. xylophilus . Furthermore, depletion of Mn-SOD decreased fecundity and virulence of Bu. xylophilus, while the insulin pathway is significantly affected. Thus, we propose that destructive pathogenicity of Bu. xylophilus to pines is partly owing to upregulated fecundity modulated by the insulin pathway in association with the ROS pathway and further enhanced by H2 O2 oxidative stress. These findings provide a better understanding of pathogenic mechanisms in plant–pathogen interactions and adaptive evolution of invasive species. This article is part of the theme issue 'Biotic signalling sheds light on smart pest management'.